RESEPSI HEROISME NOVEL SANG PENGGESEK BIOLA KARYA YUDHI HERWIBOWO BERDASARKAN INTERPRETASI GENDER - Dimas Pramata Sukma; Nazla Maharani Umaya; Harjito Harjito (Lembaga Pengembangan Kinerja Dosen, 2022)
The problems of this research are (1) How is the reception of students of SMK Negeri 1 Dukuhturi regarding the ideology of heroism in the novel Sang Penggesek Biola?, (2) How is the ideology of heroism in the novel Sang Penggesek Biola?. The objectives of this study are (1) Describe the reception of students of SMK Negeri 1 Dukuhturi regarding the ideology of heroism in the novel Sang Penggesek Biola, (2) Describe the content of the ideology of heroism in the novel Sang Penggesek Biola. The research population was 32 students. Data collection methods used are interviews, questionnaires, and researcher notes. Data analysis used descriptive qualitative. Based on the results of the study, it is known that the reception of female gender and male gender has similarities and differences. This is because the female gender carries her feelings while the male gender focuses on the impact of an event on the plot. In line with that, Yudhi Herwibowo's novel Sang Penggesek Biola has an ideology of heroism that can be seen through the thoughts of the main characters